2018
DOI: 10.22230/ijepl.2017v12n8a792
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in participatory leadership: An examination of principals’ time spent working with others

Abstract: The purpose of this study was to examine whether female principals have a more participatory style compared to their male counterparts by examining principals' daily time allocation patterns. The study analyzed data from End of Day (EOD) survey logs from principals in an urban school district in the United States. Results from hierarchical linear modeling (HLM) showed that female principals, when compared to male principals, spent a higher proportion of their time working with others in planning/setting goals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…This way of thinking confirms the definition of leadership that emphasizes the power of influence, especially individually, not structural influences [19]. Responsibility is a hallmark of performance-oriented leaders [20], in addition, sensitivity to humanitarian issues such as gender [21] and harmony [22].…”
Section: Human Resource Leadershipsupporting
confidence: 71%
“…This way of thinking confirms the definition of leadership that emphasizes the power of influence, especially individually, not structural influences [19]. Responsibility is a hallmark of performance-oriented leaders [20], in addition, sensitivity to humanitarian issues such as gender [21] and harmony [22].…”
Section: Human Resource Leadershipsupporting
confidence: 71%
“…Since individuals commonly refer to visible attributes such as gender, to form the basis of their evaluations of and beliefs about the characteristics of others, dyadic gender composition plays a key role in determining the beliefs and expectations of principal–middle leaders’ interpersonal interactions (Phillips et al ., 2009) and therefore may influence PST attribute. The female leadership style has been characterized as collaborative and supportive, with interpersonal relationships that are collegial and caring, promoting cooperation over competition, and tending to solve problems through negotiation and compromise (Sebastian and Moon, 2017). PST involves activities that are characterized by a more participatory (e.g.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The strong similarities between the sexes on the three factors indicated in the results in this work do not match findings from previous research in the field. For example, studies by Coronel, Moreno and Carrasco [92], Sebastian and Moon [93] and Lorentzen [94] demonstrated that female principals tend to have better attitudes and stronger beliefs regarding inclusive educational issues and cooperative methodologies than their male counterparts. Authors such as Vestal and Torres [95], Randall and West [96], and Hauseman [97] pointed out that, in this sense, the special sensitivity of women principals towards the well-being and integration of students in the educational institution could be a factor that explains these differences between male and female principals.…”
Section: Discussionmentioning
confidence: 99%